2016
DOI: 10.1002/adma.201602748
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Intracellular Production of Reactive Oxygen Species by a 2D Molybdenum Disulfide Glycosheet

Abstract: A 2D "glycosheet" based on supramolecular self-assembly between 2D MoS and fluorescent glycoligands is developed. The composite 2D material is proven suitable for targeted intracellular production of reactive oxygen species (singlet oxygen) by the sequential control of a receptor endocytosis and light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 52 publications
5
72
0
Order By: Relevance
“…Within them, DCM‐galactose and coumarin‐mannose on GO were used for the simultaneous detection of PNA/Con A with a single excitation and dual emission . 2D MoS 2 was used along with GO to load a DCM‐galactose probe for staining Hep‐G2 cells and imaging intracellular ROS production . The imaging abilities of GO and MoS 2 were measured, and indicated that MoS 2 significantly enhanced fluorescence imaging compared to GO (Figure 18c).…”
Section: Carbohydrate‐conjugated Nanomaterialsmentioning
confidence: 99%
“…Within them, DCM‐galactose and coumarin‐mannose on GO were used for the simultaneous detection of PNA/Con A with a single excitation and dual emission . 2D MoS 2 was used along with GO to load a DCM‐galactose probe for staining Hep‐G2 cells and imaging intracellular ROS production . The imaging abilities of GO and MoS 2 were measured, and indicated that MoS 2 significantly enhanced fluorescence imaging compared to GO (Figure 18c).…”
Section: Carbohydrate‐conjugated Nanomaterialsmentioning
confidence: 99%
“…Due to the intrinsic ROS‐producing ability of photosensitizers through light irradiation, PDT (photodynamic therapy) has been developed as a noninvasive strategy for disease therapy . Smart drug delivery systems that can produce ROS under light illumination, and release therapeutic agents in response to the ROS produced, have been developed.…”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%
“…Smart drug delivery systems that can produce ROS under light illumination, and release therapeutic agents in response to the ROS produced, have been developed. These systems are based on the loading of known photosensitizers (which could produce 1 O 2 ) into nanoparticles, resulting in combined chemo‐ and photodynamic therapy when coloaded with drugs …”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%
“…These strongly fluorescent nanosheets can be internalized within cells, demonstrating potential applications as a cell‐targeted labeling agent . Furthermore, the cellular uptake efficacy could be further improved by conjugation of specific targeting groups . Recently, it was found that agonist‐induced activation and endocytosis of G protein‐coupled receptors (GPCRs) are significant for numerous physiological and pathological processes.…”
Section: Interactions Between Other 2d Materials and Biointerfacesmentioning
confidence: 99%